Some Considerations of Democracy and Science in the political Philosophy of Jean-Jacques Rousseau - Giannis, Vassilios (My University, 1976)
This thesis is a comparative study of Rousseau's Premier Discours and-Du Contract Social. The essay will attempt to establish the thesis that science is both indispensable and dangerous to a democratic order. Democracy, we assume, presupposes self-restraint, more specifically, the self-restraint of the few best citizens. The question then is-·does science support those virtues by which men may be persuaded to serve democracy or, quite the contrary, to destroy it?
Keywords: Political Science; Political Science